A historical analysis of Satiric verses on the administrative history of Gondar Province (1974-1991) - Damtew, Ebrahim (Ethiopian Renaissance Journal of Social Sciences and the Humanities, 2023)
Although orality and oral culture is predominant in the daily life of the people of Ethiopia, for long the historiogrtaphy of the country has neglected it to comprehend the the people’s past. In response of this call ,this study aimed at investigating certain aspects of the history of political and social grievances of the people as reflected in oral verses in Gondar province during (1974-1991). The study is descriptive in nature and employed satire for analysis. The poems were collected through various data collection methods. The main ones are interviews, primary and secondary document analysis. The findings from the poems adhere to leading political personalities in the province, their policies, approaches and the state itself. The dynamic relationship, public reaction to the state policies, grievances, inner feelings, expressions, unheard voices towards the revolution and the Derg were some among others. The continuity of poetic tradition is also reflected in the messages of the poems. The poems are generally shed light about public curiosity, critical observation of the revolutionary reforms and their implementations. For development to occur, it is imperative to involve everyone to participate genuinely in the affair of his /her locality and the country at large. In line with this, the earlier hopes in the revolution are eroded as the civil warwith out clear national picture spread rampantly throughout the nation. The poems reflect the uneasy relation of the state and the wider public at least in Gondar province that ultimately brought about the down fall of the military government and continuity of crisis in the nation.